New method for real-time visualization and quantitative characterization of early colorectal cancer in endoscopy: a pilot study - Wagner, Andrej; Zandanell, Stephan; Ziachehabi, Alexander; Mitrakov, Alexander; Klieser, Eckhard; Neureiter, Daniel; Kiesslich, Tobias; Mayr, Christian; Berr, Frieder; Fedoruk, Michael; Singhartinger, Franz; Holzinger, Josef (Endoscopy International Open, 2022)
Background and study aims Endoscopic optical diagnosis is crucial to the therapeutic strategy for early gastrointestinal cancer. It accurately (> 85 %) predicts pT category based on microsurface (SP) and vascular patterns (VP). However, interobserver variability is a major problem. We have visualized and digitalized the graded irregularities based on bioinformatically enhanced quantitative endoscopic image analysis (BEE) of high-definition white-light images.Methods In a pilot study of 26 large colorectal lesions (LCLs, mean diameter 39 mm), we retrospectively compared BEE variables with corresponding histopathology of the resected LCLs.Results We included 10 adenomas with low-grade intraepithelial neoplasia (LGIN), nine with high-grade intraepithelial neoplasia (HGIN) and early adenocarcinoma (EAC), and seven deeply submucosal invasive carcinomas. Quantified density (d) and nonuniformity (CU) of vascular and surface structures correlated with histology (rs d VP: –0.77, rs CU VP: 0.13, rs d SP: –0.76, and rs CU SP: 0.45, respectively). A computed BEE score showed a sensitivity and specificity of 90 % and 100 % in the group with LGINs, 89 % and 41 % in the group with HGINs and EACs, and 100 % and 95 % in the group with deeply invasive carcinoma, respectively.Conclusions In this pilot study, BEE showed promise as a tool for endoscopic characterization of LCLs during routine endoscopy. Prospective clinical studies are needed.